Health-Related Quality of Life Among People Aged ≥65 Years with Self-reported Visual Impairment: Findings from the 2006–2010 Behavioral Risk Factor Surveillance System - Crews, John E. (Ophthalmic Epidemiol, 2014)
PURPOSE: To examine the association between health-related quality of life (HRQoL) and visual impairment among people aged ≥65 years. METHODS: We used cross-sectional data from the 2006–2010 Behavioral Risk Factor Surveillance System to examine six HRQoL measures: self-reported health, physically unhealthy days, mentally unhealthy days, activity limitation days, life satisfaction, and disability. Visual impairment was categorized as no, a little, and moderate/severe. We examined the association between self-reported visual impairment and HRQoL using logistic regression accounting for the survey’s complex design. RESULTS: People with self-reported moderate/severe visual impairment had more frequent (≥14) physically unhealthy days, mentally unhealthy days, and activity limitation days in the last 30 days compared to those reporting a little or no visual impairment. After controlling for all covariates (age, sex, marital status, race/ethnicity, education, income, diabetes, heart disease, stroke, heart attack, body mass index, leisure time activity, smoking, and medical care cost concerns) and comparing to those with no self-reported visual impairment, people reporting a little visual impairment were more likely to have fair/poor health (odds ratio, OR, 1.2, 95% confidence interval, CI, 1.1–1.3), life dissatisfaction (OR 1.6, 95% CI 1.3–2.0), and disability (OR 1.5, 95% CI 1.3–1.6), and those with self-reported moderate/severe visual impairment had more fair/poor health (OR 1.8, 95% CI 1.6–2.0), life dissatisfaction (OR 2.3, 95% CI 1.8–2.9), and disability (OR 2.0, 95% CI 1.8–2.2). They also had more frequent physically unhealthy days (OR 1.9, 95% CI 1.7–2.1), mentally unhealthy days (OR 1.8, 95% CI 1.5–2.1), and activity limitations days (OR 1.9, 95% CI 1.6–2.2). CONCLUSION: Poor HRQoL is strongly associated with the severity of self-reported visual impairment among people aged ≥65 years.